EFFECT OF LEARNING EVALUATION (ORAL TEST) ON THE LEARNING OUTCOMES OF FEMALE STUDENTS KULLIYYATUL MUBALLIGHAAT AL-ISLAMIYYAH AL-ISHLAH BONDOWOSO SCHOOL YEAR 2020/2021M - Agusyanto; Laila, Nur (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2022)
The purpose of this study was to determine